Perceiving Societal Pressure To Be Happy Is Linked To Poor Well-Being, Especially in Happy Nations - Rhee, J Joshua; Peker, Müjde; Becker, Maja; Bilewicz, Michal; Bastian, Brock; Baguma, K Peter; Barry, Oumar; Dejonckheere, Egon; Baguma, Peter K. (Nature Research, 2022)
Happiness is a valuable experience, and societies want their citizens to be happy. Although this societal commitment seems laudable, overly emphasizing positivity (versus negativity) may create an unattainable emotion norm that ironically compromises individual well-being. In this multi-national study (40 countries; 7443 participants), we investigate how societal pressure to be happy and not sad predicts emotional, cognitive and clinical indicators of well-being around the world, and examine how these relations differ as a function of countries' national happiness levels (collected from the World Happiness Report). Although detrimental well-being associations manifest for an average country, the strength of these relations varies across countries. People's felt societal pressure to be happy and not sad is particularly linked to poor well-being in countries with a higher World Happiness Index. Although the cross-sectional nature of our work prohibits causal conclusions, our findings highlight the correlational link between social emotion valuation and individual well-being, and suggest that high national happiness levels may have downsides for some.
Keywords: Wellbeing; Emotion; Clinical indicator; Major clinical study; Human; Adult; Happiness; Multicenter study